Analisis Degradasi Sifat Mekanik Beton yang Ditambah Superplasticizetdan Dibakar Di Atas Suhu 300 Derajat Celcius - Agus Santoso (Universitas Negeri Yogyakarta, 2007)
The aim ofthis research is to observe the transformation ofK225 concrete cube strengthafter combusted on temperatures of300, 600 and 900 degree ofCelcius. The test was conductedon the concrete age of35 days and the mix design was added by superplasticizer to slow downthe concrete formation. The additional superplasticizer will slow down the transformation ofCalciumhydroxide (Ca(OH)) into Calciumoxyde (CaD), so it will lessen the reduction ofconcretecube strength due to combustion.